Kulturübersetzung als interaktive Praxis: Die frühe deutsche Ethnologie im Amazonasgebiet (1884–1914) - Fernández Castro, Johanna (transcript, 2020)
Johanna Fernández Castro captures cultural translation as an interactive practice of ethnological knowledge production using the example of research on indigenous Amazonian cultures.